Family Resilience Key Components in Javanese, Bataknese, and Minangnese Married Adults: Multivariate Analysis - Veronica Kristiyani; Khusnul Khatimah; Rahmah Rezki Elvika; Lely Nur Azizah; Nurul Mukhlisah; Sri Redatin Retno Pudjiati (Universitas Ahmad Dahlan, 2024)
Indonesia has a variety of ethnicities and cultural values that shape people’s behavior in everyday life. Family resilience is one of these factors. This research aimed to examine the differences among three distinct ethnic groups in relation to key family resilience components (family belief systems, family organizational structures, and family communication patterns). A total of 672 married participants aged 19 to 65 years (Mage = 42.07, SD = 9.720) reported their family resilience using the Indonesian version of the Walsh Family Resilience Questionnaire, and the data were analyzed using multivariate analysis of variance (MANOVA) and ANOVA. The results revealed that in terms of the family belief system, Javanese people are significantly different from Minangnese and Bataknese people and are the most prevalent; in terms of the family organizational structure, only Minangnese and Bataknese people are significantly different, whereas Minangnese people are most prevalent; and in terms of family communication patterns, Javanese people are significantly very different from the others and are the most prevalent. Overall, family resilience is only significantly different for Javanese and Bataknese people, where Bataknese people have the highest level of family resilience.